Agribusiness Management Innovation; Enhancing Competitiveness in The Global Market - Olyvia Rosalia; Amruddin Amruddin (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the influence of innovation in agribusiness management on enhancing competitiveness in the global market. In the context of globalization and increasingly competitive international market dynamics, Indonesian agribusiness faces challenges not only to survive but also to compete with other countries that are more advanced in terms of technology and managerial systems. The method used is quantitative, with a survey approach targeting agribusiness actors from various business scales. The research instrument in the form of a questionnaire was developed based on four dimensions of innovation: process innovation, product innovation, managerial innovation, and marketing innovation. Data analysis was carried out using multiple linear regression to determine the extent to which each innovation variable affects agribusiness competitiveness. The research findings indicate that all four types of innovation simultaneously and partially have a positive and significant influence on competitiveness in the global market. These findings emphasize the importance of an innovative management approach in future agribusiness development strategies. The practical implication of this research is the need for policy support that fosters an innovation ecosystem, enhances business actors' capacity, and provides access to modern technology to sustainably strengthen the position of Indonesian agribusiness in the global market.